TEACHERS' PEDAGOGIC COMPETENCE IN DEVELOPING STUDENTS' CRITICAL THINKING ABILITIES IN ELEMENTARY SCHOOLS - Muammar Muammar (El Midad, 2024)
This research is motivated by the demands of the world of education to develop student's critical thinking skills early on. This study aims to describe the contribution of teachers' pedagogical competence in developing students' critical thinking skills in elementary schools. This type of research is descriptive with a qualitative approach. The research setting is at SDIT Anak Sholeh Mataram. The data collection procedure uses observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and data verification. Data validity checking with triangulation techniques and sources. The results of the study indicate that the contribution of teachers' pedagogical competence in developing students' critical thinking skills at SDIT Anak Sholeh Mataram is carried out through various active participatory learning activities, such as (a) knowing in detail problems; (b) being able to identify problems; (c) being able to distinguish relevant and irrelevant ideas; (d) being able to distinguish facts from non-facts; (e) being able to distinguish between constructive and non-constructive criticism; (f) identifying attributes of humans, places, and objects; (g) being able to see a way out of the problem; (h) being able to connect one problem to another; (i) being able to make predictions from the information presented; (k) able to distinguish between wrong and correct conclusions; and (l) able to conclude.